2020
DOI: 10.1017/s0025315420000818
|View full text |Cite
|
Sign up to set email alerts
|

Lithology could affect benthic communities living below boulders

Abstract: Structure and diversity of sessile zoobenthic assemblages seem to be driven not only by chemical-physical constraints and biological interactions but also by substrate lithology and its surface features. Nevertheless, broadly distributed crustose epilithic corallines could mask the role of substrate on animal settling. To evaluate the direct influence of different rocky substrates, occurrence and coverage of several sessile species, growing on the dark (i.e. coralline-free) face of sublittoral limestone and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…5 B). A similar effect was registered in a recent study comparing sessile assemblages in natural limestone and granite boulders conducted in Sardinia, Mediterranean Sea (Canessa et al, 2020). In this case, limestone had a lower benthic coverage and different assemblage structure than granite, which could be explained by the lower surface stability of the former.…”
Section: Tablesupporting
confidence: 86%
See 2 more Smart Citations
“…5 B). A similar effect was registered in a recent study comparing sessile assemblages in natural limestone and granite boulders conducted in Sardinia, Mediterranean Sea (Canessa et al, 2020). In this case, limestone had a lower benthic coverage and different assemblage structure than granite, which could be explained by the lower surface stability of the former.…”
Section: Tablesupporting
confidence: 86%
“…Substratum material influence marine assemblages, although it generally plays a secondary role in the successional patterns, composition, and diversity of benthic assemblages compared to other environmental variables, such as food and larvae abundance, hydrodynamic exposure, and substrate orientation and microtopography (Liversage et al, 2014;Coombes et al, 2015;Canessa et al, 2019Canessa et al, , 2020. Therefore, the compounding and interplay of multiple factors and environmental conditions hinder our ability to assess the role of material on marine assemblages, particularly in heterogeneous and patchy ecosystems such as rocky shores (Raffaelli and Hawkins, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although red coral is found both on coralligenous accretions and primary rocks, it shows a preference for biogenic habitats. It is known that the presence of a coralline algal layer can positively or negatively drive the settling of many benthic species in both tropical and temperate environments (Harrington et al, 2004;Ritson-Williams et al, 2009, 2014Canessa et al, 2020). To date, experimental tests have shown that red coral larval settling did not show significant differences between Lithophyllum stictaeforme and bare rocks (Zelli et al, 2020); however, this approach should be applied to different crustose algae.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, information from shallow water environments (0-10 m water depth) is scarce since they are often influenced by strong waves impeding field surveys. Few studies concerning stone habitats in shallow waters exist, e.g., from the Mediterranean Sea in water depths between 15-20 m, where it was shown that instability of rocky substrates and their lithology can influence colonization [31]. Diverse studies on benthic community structure indicate a strong correlation between biodiversity and physical habitat structure [32][33][34][35], which can be assumed to be pronounced in the most dynamic shallow water environments.…”
Section: Introductionmentioning
confidence: 99%